Ametropia and ambliopia in students of 42 schools of the program Healthful Schools in DISA II, Lima. Peru, 2007-2008 - Carrión Ojeda, Carlos (2009)
Background: There are almost 12 million children in Peru, and no studies regarding the prevalence of ametropia or amblyopia in school children have ever been reported.Objetives: To determine the epidemiologic characteristics and current therapy strategies for severe ametropia and amblyopia in students from limited-resource families in Southern Lima, Peru.Material and methods: A significant sample representative of 120,000 children from 42 schools in five districts of Southern Lima was assessed. The study was performed in three stages. The first one was a cross-sectional and observational survey, assessing visual acuity and performing refraction testing in 12,364 students. The second stage consisted in follow-up assessments in students with moderate and severe ametropy, aiming to confirm their ametropy degree and its respective cyclopegic refraction. The third stage detected students with amblyopia if visual acuty could not be corrected with the best prescription for wearing eyeglasses; we looked for a relationship between severe ametropy and amblyopia, and we determined whether the children had any eyeglasses prescription as initial therapy for amblyopia. Excel 2003 software was used for calculating sample size and for analyzing results obtained.Results: We found a high prevalence of ametropia (46,3%) (p <0,01) in the general school children population and a high prevalence of amblyiopia in those children with severe ametropy (39%). Four children out of ten with severe ametropy had developed amblyopia (p< 0,029); and of 90,25% of them did not wear eyeglasses (p< 0.045).Conclusion: It is urgent to make prevention interventions for amblyopia before 5 years of age, since this condition may still be reversible at that age. We also postulate that infantile malnutrition may be a risk factor for the development of ametropy, as it is the case for a poor academic performance.